2010
DOI: 10.1177/0891988709351804
|View full text |Cite
|
Sign up to set email alerts
|

Association of Apolipoproteins E4 and C1 With Onset Age and Memory: A Study of Sporadic Alzheimer Disease in Taiwan

Abstract: We conclude that the e4 allele affects neuropsychological performance and illness morbidity. Concomitantly, ApoE e4 and APOC1 A alleles have a better association with AD than ApoE e4 alone. In addition, APOC1 may partially contribute to the pathogenesis of AD, but the nature of its relationship with e4 requires further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 35 publications
(46 reference statements)
2
15
0
Order By: Relevance
“…Several authors have attempted to answer this question by conducting analyses of haplotypes of this cluster. Although no consensus has been reached concerning this issue, it appears that a greater number of studies support the hypothesis that the -317*ins allele of the APOC1 gene is a second susceptibility allele, rather than the possibility that this allele is simply inherited together with the E*4 allele of the APOE gene [4,23,24]. Our data also agree with those authors, since they demonstrate that the -317*ins allele of the APOC1 gene is more common among patients than controls even in the presence of the E*3 allele of the APOE gene, which does not cause increased susceptibility to Alzheimer's (Table 2).…”
Section: Discussionmentioning
confidence: 92%
“…Several authors have attempted to answer this question by conducting analyses of haplotypes of this cluster. Although no consensus has been reached concerning this issue, it appears that a greater number of studies support the hypothesis that the -317*ins allele of the APOC1 gene is a second susceptibility allele, rather than the possibility that this allele is simply inherited together with the E*4 allele of the APOE gene [4,23,24]. Our data also agree with those authors, since they demonstrate that the -317*ins allele of the APOC1 gene is more common among patients than controls even in the presence of the E*3 allele of the APOE gene, which does not cause increased susceptibility to Alzheimer's (Table 2).…”
Section: Discussionmentioning
confidence: 92%
“…Of the 44 full-text articles, 30 were further excluded for various reasons ( Figure 1 ). Fourteen case-control articles met the preliminary inclusion criteria [9], [10], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23]. The study by Chartier-Harlin et al .…”
Section: Resultsmentioning
confidence: 99%
“…[23]. The most common AD diagnostic criteria was from NINCDS-ADRDA [10], [12], [14], [16], [17], [18], [19], [20], [21], [22], [23]. Four studies [9], [15], [17], [21] used the Diagnostic and Statistical Manual of Mental Disorders, third/fourth edition (DSM-III-R or DSM-IV) criteria, and one study [22] used the International Classification of diseases, Tenth Revision (ICD-10).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies from China, APOE ε4 has been correlated with AD risk [7,3537], as well as cognitive decline and memory performance in mild cognitive impairment (MCI) [3840]. Neuroimaging studies found smaller hippocampal volumes in symptomatic ε4 carriers [35,41], but not among cognitively normal ε4-carrying controls [35].…”
Section: Introductionmentioning
confidence: 99%